(untitled) (Innovative professional education, 2022)
The educational and professional program of professional development is a system of educational components of the professional development of scientific and pedagogical workers of institutions of vocational pre-higher education. The educational and professional program of professional development is a regulatory document for the organization of the educational process for various categories of students at the University of Education Management